Pivoting a Large Object: Whole-Body Manipulation by a Humanoid Robot - E. Yoshida; P. Blazevic; V. Hugel; K. Yokoi; K. Harada (Applied Bionics and Biomechanics)
In this article, we present a method of whole-body manipulation of large objects by a humanoid robot using a pivoting motion. Pivoting manipulation can be an alternative to pushing or lifting for more dexterous and stable operation, which is often used by humans to move large and bulky furniture. This article describes a method and control techniques for a humanoid robot to perform the manipulation of a large object through whole-body motion by applying this pivoting motion. For this purpose, first the object is manipulated by two arms of a humanoid robot using impedance control for grasping, together with body balancing control while the robot stays at the same place. Next, the movement of the humanoid robot itself is performed by stepping motion with the help of resolved momentum control to guarantee the robot stability. The proposed manipulation is validated through dynamic simulation and real hardware experiment of the humanoid robot HRP-2 performing the pivoting task.